A method for synthesizing rare earth-magnesium-nickel ternary micro-nano alloy particles

CN122746472APending Publication Date: 2026-09-15PEKING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611179063.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-09-15

AI Technical Summary

Technical Problem

1、高温熔炼法:反应温度需1100℃以上,且需900~950℃高温退火4h以上,能耗极高;镁的蒸气压在高温下急剧升高,导致镁元素大量挥发,合金成分难以精确调控;镁蒸气冷凝后形成的超细镁粉也存在爆炸安全隐患

Benefits of technology

[0017] The method for synthesizing rare earth-magnesium-nickel ternary micro/nano alloy particles provided by this invention has the following beneficial effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122746472A_ABST
    Figure CN122746472A_ABST
Patent Text Reader

Abstract

This invention discloses a method for synthesizing rare earth-magnesium-nickel ternary micro / nano alloy particles, belonging to the field of hydrogen storage alloy material preparation technology. The method includes: RENi5 nanoparticles, a magnesium source, and REH... x Powder, KCl-NaCl-CaCl2 molten salt, and CaH2 are mixed and ground thoroughly under argon protection. The mixture is then placed in a reaction vessel and heated to 120°C under argon protection to dehydrate the product. Further heating to 600°C and holding at this temperature yields AB2-type RE. 2‑y Mg y Ni4 alloy; further heating to 800℃ and holding at that temperature will yield AB3 type RE. 3‑y Mg y Ni9 alloy. After the reaction, the product is cooled and removed under an argon atmosphere for post-processing. This invention enables the rapid preparation of RE-Mg-Ni micro / nano alloy particles with controllable composition under mild conditions of 600-800℃, completely solving the problems of magnesium volatilization and composition control, while significantly improving hydrogen storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hydrogen storage alloy material preparation technology, specifically to a method for synthesizing rare earth-magnesium-nickel ternary micro / nano alloy particles. Background Technology

[0002] Rare earth-magnesium-nickel (RE-Mg-Ni) ternary alloys, possessing both the excellent kinetic properties of rare earth hydrogen storage alloys and the high hydrogen storage density of magnesium-based alloys, are among the most promising next-generation hydrogen storage materials, with important applications in gaseous hydrogen storage and nickel-metal hydride battery anode materials. Among them, AB2-type RE... 2-x Mg x Ni4 and AB3 type RE 3-x Mg x The theoretical hydrogen storage density of Ni9 alloy can reach 1.6~1.8 wt%, significantly higher than that of traditional AB5 type LaNi5 alloy (hydrogen storage density 1.37 wt%), while also exhibiting good hydrogen absorption and desorption performance at room temperature. Currently, the mainstream preparation methods for RE-Mg-Ni alloys suffer from the following core drawbacks: 1. High-temperature smelting method: The reaction temperature needs to be above 1100℃, and high-temperature annealing at 900~950℃ for more than 4 hours is required, which consumes a lot of energy; the vapor pressure of magnesium increases sharply at high temperature, resulting in a large amount of magnesium volatilization, and the alloy composition is difficult to control precisely; the ultrafine magnesium powder formed after magnesium vapor condensation also poses an explosion safety hazard.

[0003] 2. Powder metallurgy: The precursor alloy needs to be crushed and sintered at high temperature for a long time. It also has the problem of magnesium volatilization. In addition, the product is a bulk material, which needs to be crushed and ground later. It is easy to introduce impurities and has poor kinetic properties.

[0004] 3. Mechanical alloying method: The degree of alloying is low, and it is easy to generate amorphous phase and impurity phase. The cycle stability is poor and it is difficult to scale up production. Summary of the Invention

[0005] The purpose of this invention is to address the aforementioned problems in the existing technology by providing a novel method for synthesizing rare earth-magnesium-nickel ternary micro / nano alloy particles. By utilizing molten salt-assisted low-temperature synthesis, RE-Mg-Ni micro / nano alloy particles with controllable composition can be rapidly prepared under mild conditions of 600~800℃, completely solving the problems of magnesium volatilization and composition control, while significantly improving the hydrogen storage kinetics performance of the material.

[0006] The technical solution of this invention is as follows: This invention provides a method for synthesizing rare earth-magnesium-nickel ternary micro / nano alloy particles, comprising the following steps: (1) Ingredients and mixing: RENi5 nanoparticles, magnesium source, REH xThe powder, KCl-NaCl-CaCl2 molten salt and CaH2 are mixed and ground evenly under argon protection, and then loaded into a reaction vessel; The magnesium source is nano-Mg powder passivated in an argon atmosphere, or the magnesium source is a Mg-NaCl dispersion obtained by mixing Mg powder and NaCl and then ball milling in an argon atmosphere. The RE is La, Ce, Pr, or Nd; The REH x In the powder, x = 1.8~3.0; The KCl-NaCl-CaCl2 molten salt is prepared by mixing and drying CaCl2, NaCl, and KCl. (2) Molten salt reaction: Place the reaction vessel in a heating device, raise the temperature to 100~150℃ under argon protection and keep it at that temperature to remove adsorbed water; then select the following operations as needed: When it is necessary to synthesize AB2 type RE 2-y Mg y When processing Ni4 alloy, after removing adsorbed water, continue to heat to 550~700℃ and hold at that temperature. When it is necessary to synthesize AB3 type RE 3-y Mg y When processing Ni9 alloy, after removing adsorbed water, first raise the temperature to 550~700℃ and hold it, then continue to raise the temperature to 800~1000℃ and hold it. The RE 2-y Mg y Ni4 or RE 3-y Mg y In Ni9, y = 0.8~1.2; (3) Post-processing: After the molten salt reaction is completed, cool to room temperature, remove the product under an argon atmosphere, wash to remove the KCl-NaCl-CaCl2 molten salt, centrifuge, wash with anhydrous ethanol, and vacuum dry. Rare earth metals are easily hydrolyzed, and ethanol can ensure purity. Vacuum drying is more conducive to preventing oxidation.

[0007] Optionally or preferably, in step (1), the magnesium source preparation method includes, but is not limited to, the following two schemes: Option 1: Prepare nano-Mg powder (particle size 50~200nm) by hydrogen plasma arc method, passivate in argon atmosphere for 24h and then store; Option 2: Commercial Mg powder (50~100 mesh) and NaCl are mixed at a preset mass ratio and ball-milled at 250 rpm for 2.5 h under an argon atmosphere to obtain a Mg-NaCl dispersion.

[0008] Optionally or preferably, in step (1), REH xPowder preparation methods include, but are not limited to, the following: commercial rare earth powder is hydrogenated at 200℃ and 4MPa H2 for 4 hours to obtain REH. x powder.

[0009] Optionally or preferably, the method for preparing KCl-NaCl-CaCl2 molten salt in step (1) includes, but is not limited to, the following scheme: CaCl2, NaCl and KCl are mixed in a preset molar ratio and dried under vacuum at 120°C for 12 hours to obtain a eutectic salt (melting point ≈ 550°C).

[0010] Optionally or preferably, in step (1), the amount of KCl-NaCl-CaCl2 molten salt added is RENi5 nanoparticles, a magnesium source, and REH. x The amount of CaH2 added is 1.5 to 2.0 times the total mass of the powder; the amount of CaH2 added is RENi5 nanoparticles, magnesium source and REH. x 30% to 50% of the total powder mass.

[0011] Optionally or preferably, in step (1), when preparing the KCl-NaCl-CaCl2 molten salt, the molar ratio of CaCl2, NaCl, and KCl is 50:30:20.

[0012] Optionally or preferably, in step (1), the mass ratio of Mg powder to NaCl in the Mg-NaCl dispersion is 1:5 to 1:9.

[0013] Optionally or preferably, in steps (1) and (2), the reaction vessel can be an alumina boat, and the heating equipment can be a tube furnace.

[0014] Optionally or preferably, in step (2), the holding time is 1h when the temperature is raised to 100-150℃, 4h when the temperature is raised to 550-700℃, and 2h when the temperature is raised to 800-1000℃; the heating rate is 4℃ / min.

[0015] Optionally or preferably, step (3) further includes the following steps: washing the vacuum-dried product with 0.1 mol / L dilute acetic acid to further remove surface oxides, then washing with water and drying.

[0016] Optionally or preferably, the RENi5 nanoparticles, magnesium source, and REH are controlled by the following formula A or B. x The molar ratio of the powders was adjusted to obtain rare earth-magnesium-nickel ternary micro / nano alloys with different crystal forms: Formula A: 0.8 RENi5+ y Mg + (1.2-y) REH x = RE 2-y Mg yNi4+ (1.2-y)x / 2 H2, where y=0.8~1.2, is an AB2 type rare earth-magnesium-nickel alloy; Formula B: 1.8 RENi5+ y Mg + (1.2-y) REH x = RE 3-y Mg y Ni9+ (1.2-y)x / 2 H2, where y=0.8~1.2, is an AB3 type rare earth-magnesium-nickel alloy.

[0017] The method for synthesizing rare earth-magnesium-nickel ternary micro / nano alloy particles provided by this invention has the following beneficial effects.

[0018] 1. Mild reaction conditions: This invention uses RENi5 nanoparticles as a precursor, a magnesium source, and REH... x Using molten salt as the core raw material to form a molten salt synthesis system, the reaction temperature is only 600~1000℃, and 800℃ is generally sufficient, which is far lower than the traditional smelting method (>1100℃). Energy consumption is reduced by more than 60%, solving the problem of high temperature and high energy consumption in the traditional method.

[0019] 2. Precise composition control: This invention uses a ternary eutectic salt of KCl-NaCl-CaCl2 (melting point about 550℃) as the reaction medium, which can effectively suppress magnesium volatilization. Combined with CaH2, it provides a strong reducing atmosphere. ICP test shows that the deviation between the product element ratio and the feed ratio is <5%, and the composition control is precise, which solves the problems of serious magnesium volatilization and low composition control precision in traditional methods.

[0020] 3. Fast reaction speed: In the molten salt reaction of this invention, the reaction time required to generate AB2 type alloy product is 4 hours and the reaction time required to generate AB3 type alloy product is 6 hours (the synthesis of AB3 type alloy adopts a two-step heating method, the first step is to synthesize AB2 intermediate at 550~700℃, and the second step is to generate AB3 by solid-state reaction at 800~1000℃). The time is much shorter than the 12~24 hours of the traditional method, which improves the generation efficiency.

[0021] 4. Excellent performance of alloy products: The alloy products prepared by this invention are micro-nano particles of 100nm~5μm with a large specific surface area. They can complete the first round of hydrogen absorption within 1 minute at 30℃ and 4MPa H2 without activation. This solves the problem of poor hydrogen absorption and desorption kinetics of traditional bulk alloys and the need for multiple high-temperature activations.

[0022] 5. Safe and controllable process: This invention has no high-temperature magnesium vapor leakage, does not require high-pressure smelting equipment, is easy to scale up production, solves the safety hazards caused by magnesium vapor leakage in the traditional preparation process, and simplifies production equipment and process.

[0023] 6. Wide applicability: This invention can be extended to various light rare earth systems such as La, Ce, Pr, and Nd, and can prepare alloys with different crystal forms such as AB2 and AB3. It can be applied to a variety of fields such as high-pressure gaseous hydrogen storage systems, nickel-metal hydride battery anode materials, and organic liquid hydrogen storage dehydrogenation catalysts. Attached Figure Description

[0024] Figure 1 This is a scanning electron microscope image of the AB2-type LaMgNi4 nanoparticles prepared in Example 3.

[0025] Figure 2 This is a scanning electron microscope image of AB3-type La2MgNi9 nanoparticles from Example 5.

[0026] Figure 3 The AB2 type hydrogen storage alloy La in Example 5 1.2 Mg 0.8 Ni4, LaMgNi4, La 0.8 Mg 1.2 XRD pattern of Ni4.

[0027] Figure 4 The AB3 type hydrogen storage alloy La in Example 5 2.2 Mg 0.8 Ni9, La2MgNi9, La 1.8 Mg 1.2 XRD pattern of Ni9.

[0028] Figure 5 The AB2 type hydrogen storage alloy La in Example 5 1.2 Mg 0.8 Ni4, LaMgNi4, La 0.8 Mg 1.2 Hydrogen absorption kinetics curve of Ni4.

[0029] Figure 6 The AB3 type hydrogen storage alloy La in Example 5 2.2 Mg 0.8 Ni9, La2MgNi9, La 1.8 Mg 1.2 Hydrogen absorption kinetics curve of Ni9. Detailed Implementation

[0030] To enable those skilled in the art to better understand the present application, the present application will be clearly and completely described below with reference to embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of the present application, and not all embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present application. Unless otherwise specified, the instruments, equipment, and reagents used in the embodiments are all from commercial channels.

[0031] Example 1: AB2 type La 0.8 Mg 1.2 Preparation of Ni4 micro / nanoparticles (using nano-Mg powder as the magnesium source) 1. Raw material preparation: Nano-Mg powder: prepared by hydrogen plasma arc method, with a particle size of 50~150nm, and passivated in argon atmosphere for 24h; LaNi5 nanoparticles: prepared in the laboratory, with a particle size of 50~100nm; LaH3 powder: commercial La powder was hydrogenated at 200℃ and 4MPa H2 for 4h; KCl-NaCl-CaCl2 molten salt: CaCl2:NaCl:KCl=50:30:20 (molar ratio), vacuum dried at 120℃ for 12h.

[0032] 2. Ingredients and Mixing: Weigh 1.081g of LaNi5 nanoparticles, 0.090g of nano-Mg powder, 2.0g of KCl-NaCl-CaCl2 molten salt, and 0.5g of CaH2, grind and mix them evenly in an argon glove box, and then load them into an alumina boat.

[0033] 3. Molten salt reaction: The corundum boat is placed in a tube furnace, and under argon protection at a rate of 70 mL / min, the temperature is increased to 120℃ at a rate of 4℃ / min and held for 1 hour, and then increased to 600℃ at a rate of 4℃ / min and held for 4 hours.

[0034] 4. Post-processing: After the molten salt reaction is completed, the product is naturally cooled to room temperature, and then washed three times with deionized water to remove the KCl-NaCl-CaCl2 molten salt. The product after centrifugation is washed twice with anhydrous ethanol and dried under vacuum at 60°C for 12 hours to obtain a gray-black powder, which is the AB2 type rare earth-magnesium-nickel ternary micro-nano alloy particle.

[0035] 5. Product Characterization XRD characterization: The product is pure-phase La. 0.8 Mg 1.2 Ni4, space group F-43m, cell parameter a = 7.161 Å; ICP elemental analysis: La:Mg:Ni = 0.88:1.20:4, consistent with the feed ratio; SEM / TEM: Particle size 100~250nm, uniform elemental distribution; Hydrogen storage performance: At 30℃ and 4MPa H2, the hydrogen absorption capacity reaches 1.59wt% within 1 minute, and the reversible hydrogen storage capacity is 1.12wt% at 100℃.

[0036] Example 2 AB3 type La 1.8 Mg 1.2 Preparation of Ni9 nanoparticles (using nano-Mg powder as the magnesium source). 1. Raw material preparation: Same as in Example 1.

[0037] 2. Ingredients and Mixing: Weigh 1.081g of LaNi5 nanoparticles, 0.040g of nano Mg powder, 0.172g of LaH3 powder, 2.0g of KCl-NaCl-CaCl2 molten salt, and 0.5g of CaH2. Grind and mix them evenly in an argon glove box and then load them into an alumina boat.

[0038] 3. Molten salt reaction: The corundum boat is placed in a tube furnace, and under argon protection at a rate of 70 mL / min, the temperature is increased to 120℃ at a rate of 4℃ / min and held for 1 hour. Then, the temperature is increased to 600℃ at a rate of 4℃ / min and held for 4 hours. Finally, the temperature is increased to 800℃ at a rate of 4℃ / min and held for 2 hours.

[0039] 4. Post-processing: The post-processing was the same as in Example 1, resulting in a gray-black powder, which is AB3 type rare earth-magnesium-nickel ternary micro-nano alloy particles.

[0040] 5. Product Characterization XRD characterization: The main phase of the product is La. 1.8 Mg 1.2 Ni9, space group R-3mH, cell parameters a=4.994Å, c=24.11Å; contains small amounts of LaNi5 and LaMgNi4 impurities (total content <20%). ICP elemental analysis: La:Mg:Ni = 1.93:1.15:9; SEM: Particle size 300~500nm, elemental distribution uniform; Hydrogen storage performance: At 30℃ and 4MPa H2, the hydrogen absorption capacity in the first cycle of 3h reaches 1.15wt%, the hydrogen absorption capacity in the fifth cycle increases to 1.42wt%, and it remains at 1.31wt% after 12 cycles.

[0041] Example 3 Preparation of AB2 type LaMgNi4 nanoparticles (Mg-NaCl dispersion is the magnesium source) 1. Raw material preparation: Mg-NaCl dispersion: 0.5g of commercial Mg powder (50 mesh) and 4.5g of NaCl were mixed and ball-milled at 250rpm for 2.5h under argon atmosphere to obtain Mg-NaCl dispersion (i.e., a mixture of Mg and NaCl after ball milling under argon atmosphere, Mg:NaCl=1:9, molar ratio).

[0042] The preparation of other raw materials is the same as in Example 1.

[0043] 2. Ingredients and Mixing: Weigh 1.081g of LaNi5 nanoparticles, 0.90g of Mg-NaCl dispersion (containing 0.090g of Mg), 0.156g of LaH3 powder, 2.0g of KCl-NaCl-CaCl2 molten salt, and 0.5g of CaH2. Grind and mix them evenly in an argon glove box and then load them into an alumina boat.

[0044] 3. Molten salt reaction: The corundum boat is placed in a tube furnace, and under argon protection at a rate of 70 mL / min, the temperature is increased to 120℃ at a rate of 4℃ / min and held for 1 hour, and then increased to 600℃ at a rate of 4℃ / min and held for 4 hours.

[0045] 4. Post-processing: The post-processing was the same as in Example 1, resulting in a gray-black powder, which is the AB2 type rare earth-magnesium-nickel ternary micro-nano alloy particle.

[0046] 5. Product Characterization XRD characterization: The product is pure phase LaMgNi4, containing only a very small amount of unreacted LaNi5; ICP elemental analysis: La:Mg:Ni = 1.06:0.95:4; Hydrogen storage performance: At 30℃ and 4MPa H2, the hydrogen absorption capacity reaches 1.55wt% within 2 minutes, which is comparable to the performance of the product prepared by nano-Mg powder in Example 1.

[0047] Example 4: Preparation of AB2 type Ce-Mg-Ni ternary alloy micro / nanoparticles 1. Raw material preparation: CeNi5 nanoparticles: prepared in the laboratory, with a particle size of 50~100nm; CeH3 powder: commercial Ce powder was prepared by hydrogenation at 200℃ and 4MPa H2 for 4h; The preparation of other raw materials is the same as in Example 1.

[0048] 2. Ingredients and Mixing: According to Ce 0.8 Mg 1.2Weigh the raw materials according to the Ni4 stoichiometric ratio, including CeNi5 nanoparticles, nano-Mg powder, and CeH3 powder. After weighing, grind and mix them evenly with 2.0g of KCl-NaCl-CaCl2 molten salt and 0.5g of CaH2 in an argon glove box, and then load the mixture into an alumina boat.

[0049] 3. Molten salt reaction: The corundum boat is placed in a tube furnace, and under argon protection at a rate of 70 mL / min, the temperature is increased to 120℃ at a rate of 4℃ / min and held for 1 hour, and then increased to 600℃ at a rate of 4℃ / min and held for 4 hours.

[0050] 4. Post-processing: The post-processing was the same as in Example 1, resulting in a gray-black powder, which is the AB2 type rare earth-magnesium-nickel ternary micro-nano alloy particle.

[0051] 5. Product Characterization XRD characterization: The product is pure phase Ce. 0.8 Mg 1.2 Ni4 nanoparticles; SEM / TEM: Particle size 150~300nm, uniform element distribution; Hydrogen storage performance: At 30℃ and 4MPa H2, the hydrogen absorption capacity reaches 1.42wt% within 1 minute.

[0052] Example 5: Comparison of properties of rare earth-magnesium-nickel ternary micro / nano alloy particles prepared with different La / Mg ratios LaNi5 nanoparticles, nano-Mg powder, and LaH3 powder were weighed according to different stoichiometric ratios. Following the remaining raw materials and production steps in Examples 1-3, different rare earth-magnesium-nickel ternary micro / nano alloy particles were prepared, including the AB2 type containing La... 1.2 Mg 0.8 Ni4, LaMgNi4, La 0.8 Mg 1.2 Ni4, AB3 type including La 2.2 Mg 0.8 Ni9, La2MgNi9, La 1.8 Mg 1.2 Ni9 was characterized by XRD and its hydrogen storage performance was tested. The results are shown below: Figure 1 For La 0.8 Mg 1.2 Scanning electron microscopy (SEM) images of Ni4 micro / nano alloy particles show an average particle size of approximately 150 nm.

[0053] Figure 2 The image shows a scanning electron microscope (SEM) image of La2MgNi9 micro / nano alloy particles, revealing an average particle size of approximately 1 μm.

[0054] Figure 3The XRD patterns of AB2-type hydrogen storage alloys with different La / Mg ratios show that they all have a pure AB2 phase structure. The different La / Mg ratios cause the diffraction peaks to shift to lower angles, corresponding to the expansion of the corresponding unit cell parameters.

[0055] Figure 4 The XRD patterns of AB3-type hydrogen storage alloys with different La / Mg ratios show that they all have a pure AB3 phase structure. The different La / Mg ratios cause the diffraction peaks to shift to lower angles, corresponding to the expansion of the corresponding cell parameters.

[0056] Figure 5 The hydrogen absorption kinetics curves for AB2-type hydrogen storage alloys with different La / Mg ratios show that reducing particle size significantly improves the activation performance of the first hydrogen absorption, and nearly 100% hydrogen absorption can be completed within a few minutes without activation. The La / Mg ratio has a significant impact on its hydrogen storage performance, and the variation law is very similar to that of the AB2-type hydrogen storage alloy obtained by melting.

[0057] Figure 6 The hydrogen absorption kinetics curves for AB3-type hydrogen storage alloys with different La / Mg ratios show that reducing particle size significantly improves the activation performance of the first hydrogen absorption, and nearly 100% hydrogen absorption can be completed within a few minutes without activation. The La / Mg ratio has a significant impact on its hydrogen storage performance, and the variation law is very similar to that of the AB3-type hydrogen storage alloy obtained by melting.

[0058] The results are shown in the table below: Table 1. Hydrogen storage performance of rare earth-magnesium-nickel ternary micro / nano alloy particles with different La / Mg ratios Experimental conditions: For AB2 type alloy particles: 100℃, 4 MPa H2 hydrogen absorption / 0.1 MPa H2 hydrogen release; For AB3 type alloy particles: 30℃, 4 MPa H2 hydrogen absorption / 0.1 MPa H2 hydrogen release.

[0059] The results show that AB2 or AB3 rare earth-magnesium-nickel ternary hydrogen storage alloys with different La / Mg ratios can rapidly absorb hydrogen at room temperature without activation (the first round of hydrogen absorption is completed within 1 minute at 30℃ and 4MPa H2), exhibiting good hydrogen storage performance. They can be widely used in nickel-metal hydride battery anode materials, metal hydride solid-state hydrogen storage devices, and other fields, and have high economic value.

[0060] This article uses specific examples to illustrate the inventive concept in detail. The description of the above embodiments is only for the purpose of helping to understand the core idea of ​​the present invention. It should be noted that any obvious modifications, equivalent substitutions or other improvements made by those skilled in the art without departing from the inventive concept should be included within the protection scope of the present invention.

Claims

1. A method for synthesizing rare earth-magnesium-nickel ternary micro / nano alloy particles, characterized in that, Includes the following steps: (1) Ingredients and mixing: RENi5 nanoparticles, magnesium source, REH x The powder, KCl-NaCl-CaCl2 molten salt and CaH2 are mixed and ground evenly under argon protection, and then loaded into a reaction vessel; The magnesium source is nano-Mg powder passivated in an argon atmosphere, or the magnesium source is a Mg-NaCl dispersion obtained by mixing Mg powder and NaCl and then ball milling in an argon atmosphere. The RE is La, Ce, Pr, or Nd; The REH x In the powder, x = 1.8~3.0; The KCl-NaCl-CaCl2 molten salt is prepared by mixing and drying CaCl2, NaCl, and KCl. (2) Molten salt reaction: Place the reaction vessel in a heating device, raise the temperature to 100~150℃ under argon protection and keep it at that temperature to remove adsorbed water; then select the following operations as needed: When it is necessary to synthesize AB2 type RE 2-y Mg y When processing Ni4 alloy, after removing adsorbed water, continue to heat to 550~700℃ and hold at that temperature. When it is necessary to synthesize AB3 type RE 3-y Mg y When processing Ni9 alloy, after removing adsorbed water, first raise the temperature to 550~700℃ and hold it, then continue to raise the temperature to 800~1000℃ and hold it. The RE 2-y Mg y Ni4 or RE 3-y Mg y In Ni9, y = 0.8~1.2; (3) Post-processing: After the molten salt reaction is completed, the product is cooled to room temperature, taken out under argon atmosphere, washed to remove KCl-NaCl-CaCl2 molten salt, centrifuged and washed with anhydrous ethanol, and then vacuum dried.

2. The method according to claim 1, characterized in that, In step (1), the amount of KCl-NaCl-CaCl2 molten salt added is RENi5 nanoparticles, magnesium source and REH x The amount of CaH2 added is 1.5 to 2.0 times the total mass of the powder; the amount of CaH2 added is RENi5 nanoparticles, magnesium source and REH. x 30% to 50% of the total powder mass.

3. The method according to claim 1, characterized in that, In step (1), when preparing the KCl-NaCl-CaCl2 molten salt, the molar ratio of CaCl2, NaCl, and KCl is 50:30:

20.

4. The method according to claim 1, characterized in that, In step (1), the mass ratio of Mg powder to NaCl in the Mg-NaCl dispersion is 1:5 to 1:

9.

5. The method according to claim 1, characterized in that, In step (2), the holding time is 1h when the temperature is raised to 100~150℃, 4h when the temperature is raised to 550~700℃, and 2h when the temperature is raised to 800~1000℃; the heating rate is 4℃ / min.

6. The method according to claim 1, characterized in that, In step (3), also The process includes the following steps: washing the vacuum-dried product with 0.1 mol / L dilute acetic acid to further remove surface oxides, followed by water washing and drying.

7. The method according to any one of claims 1 to 6, characterized in that, The RENi5 nanoparticles, magnesium source, and REH can be controlled using the following formula A or B. x The molar ratio of the powders was adjusted to obtain rare earth-magnesium-nickel ternary micro / nano alloys with different crystal forms: Formula A: 0.8 RENi5+ yMg + (1.2-y) REH x = RE 2-y Mg y Ni4 + (1.2-y)x / 2 H2, where y = 0.8~1.2, is an AB2 type rare earth-magnesium-nickel alloy; Formula B: 1.8 RENi5+ y Mg + (1.2-y) REH x = RE 3-y Mg y Ni9 + (1.2-y)x / 2 H2, where y = 0.8~1.2, is an AB3 type rare earth-magnesium-nickel alloy.